After-Effects of the COVID-19 Pandemic : Prospects for Medium-Term Economic Damage - Barrett, Philip (IMF Working Papers; Working Paper, 2021)
The COVID-19 pandemic has led to a severe global recession with differential impacts within and across countries. This paper examines the possible persistent effects (scarring) of the pandemic on the economy and the channels through which they may occur. History suggests that deep recessions often leave long-lived scars, particularly to productivity. Importantly, financial instabilities-typically associated with worse scarring-have been largely avoided in the current crisis so far. While medium-term output losses are anticipated to be lower than after the global financial crisis, they are still expected to be substantial. The degree of expected scarring varies across countries, depending on the structure of economies and the size of the policy response. Emerging market and developing economies are expected to suffer more scarring than advanced economies.